(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2002)
The poet Jorge Torres in his text, Los Viajes, describes the transit through a city marked by fear and repression, a guarded place, where life seems to be under a perpetual state of siege, a scenario where history stopped without a past, no future. The speaker of the poem walks with his daughter through a city, in search of the lost ghosts, the marks capable of reconstructing an erased history (note).